Quantitative fecal immunochemical tests for colorectal cancer screening - Gies, Anton; Schrotz-King, Petra; Brenner, Hermann (International journal of cancer, 2018)
Fecal immunochemical tests (FITs) for hemoglobin (Hb) are increasingly used for colorectal cancer (CRC) screening. We aimed to review, summarize and compare reported diagnostic performance of various FITs. PubMed and Web of Science were searched from inception to July 24, 2017. Data on diagnostic performance of quantitative FITs, conducted in colonoscopy-controlled average-risk screening populations, were extracted. Summary receiver operating characteristic (ROC) curves were plotted and correlations between thresholds, positivity rates (PRs), sensitivities and specificities were assessed. Seven test brands were investigated across 22 studies. Although reported sensitivities for CRC, advanced adenoma (AA) and any advanced neoplasm (AN) varied widely (ranges: 25-100%, 6-44% and 9-60%, respectively), with specificities for AN ranging from 82% to 99%, the estimates were very close to the respective summary ROC curves whose areas under the curve (95% CI) were 0.905 (0.88-0.94), 0.683 (0.67-0.70) and 0.710 (0.70-0.72) for CRC, AA and AN, respectively. The seemingly large heterogeneity essentially reflected variations in test thresholds (range: 2-82 µg Hb/g feces) and showed moderate correlations with sensitivity (r = −0.49) and specificity (r = 0.60) for AN. By contrast, observed PRs (range: 1-21%) almost perfectly correlated with sensitivity (r = 0.84) and specificity (r = −0.94) for AN. The apparent large heterogeneity in diagnostic performance between various FITs can be almost completely overcome by appropriate threshold adjustments. Instead of simply applying the threshold recommended by the manufacturer, screening programs should adjust the threshold to yield a desired PR which is a very good proxy indicator for the specificity and the subsequent colonoscopy workload.